Hypothermia for perinatal asphyxia: trial-based resource use and costs at 6–7 years. Issue 3 (11th July 2018) - Rivero-Arias, Oliver; Eddama, Oya; Azzopardi, Denis; Edwards, A David; Strohm, Brenda; Campbell, Helen
Abstract : Objective: To assess the impact of hypothermic neural rescue for perinatal asphyxia at birth on healthcare costs of survivors aged 6–7 years, and to quantify the relationship between costs and overall disability levels. Design: 6–7 years follow-up of surviving children from the Total Body Hypothermia for Neonatal Encephalopathy (TOBY) trial. Setting: Community study including a single parental questionnaire to collect information on children's healthcare resource use. Patients: 130 UK children (63 in the control group, 67 in the hypothermia group) whose parents consented and returned the questionnaire. Interventions: Intensive care with cooling of the body to 33.5°C for 72 hours or intensive care alone. Main outcome measures: Healthcare resource usage and costs over the preceding 6 months. Results: At 6–7 years, mean (SE) healthcare costs per child were £1543 (£361) in the hypothermia group and £2549 (£812) in the control group, giving a saving of −£1005 (95% CI −£2734 to £724). Greater levels of overall disability were associated with progressively higher costs, and more parents in the hypothermia group were employed (64% vs 47%). Results were sensitive to outlying observations. Conclusions: Cost results although not significant favoured moderate hypothermia and so complement the clinical results of the TOBY Children study. Estimates were however sensitive to the care requirements of two seriously ill children in the control group. A quantification of the relationship between costs and levels of disability experienced will be useful to healthcare professionals, policy makers and health economists contemplating the long-term economic consequences of perinatal asphyxia and hypothermic neural rescue. Trial registration number: This study reports on the follow-up of the TOBY clinical trial: ClinicalTrials. gov number NCT01092637 .